Analisis Sistem Pengendalian Internal terhadap Pengaplikasian Anggaran Kegiatan dalam Menopang Efektivitas Pengelolaan Admnistrasi di Perusahaan Daerah Air Minum Tirtana Provinsi Sumatera Utara - Kayla Zahara Putri Nasada; Saparuddin Siregar (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
This study aims to analyze the internal control system for the application of the activity budget in supporting the effectiveness of administrative management at the Tirthanadi Regional Drinking Water Company, North Sumatra. This study found that the data source obtained was from secondary data, which resulted from the collection of relevant documents, including organizational structure, company operating standards, records and documents used as well as a report on the Budget for the Effectiveness of the Regional Drinking Water Company Tirtanadi. North Sumatra. This is a survey method of qualitative research. The results of this study indicate that the control system at PDAM Tirtanadi North Sumatra already meets the standard criteria developed by COSO. But it turns out that there are still a lot of things that have been revised in running the system.